Beneficial effect of recombinant human growth hormone on the intestinal mucosa barrier of septic rats - C. Yi; Y. Cao; S.R. Wang; Y.Z. Xu; H. Huang; Y.X. Cui; Y. Huang (Brazilian Journal of Medical and Biological Research, 2007)
The objective of the present study was to investigate the effects of recombinant human growth hormone (rhGH) on the intestinal mucosa barrier of septic rats and explore its possible mechanism. Female Sprague-Dawley rats were randomized into three groups: control, Escherichia coli-induced sepsis (S) and treatment (T) groups. Groups S and T were subdivided into subgroups 1d and 3d, respectively. Expression of liver insulin-like growth factor-1 (IGF-1) mRNA, Bcl-2 and Bax protein levels and the intestinal Bax/Bcl-2 ratio, and plasma GH and IGF-1 levels were determined. Histological examination of the intestine was performed and bacterial translocation was determined. rhGH significantly attenuated intestinal mucosal injuries and bacterial translocation in septic rats, markedly decreased Bax protein levels, inhibited the decrease of Bcl-2 protein expression and maintained the Bax/Bcl-2 ratio in the intestine. rhGH given after sepsis significantly improved levels of plasma GH (T1d: 1.28 ± 0.24; T3d: 2.14 ± 0.48 µg/L vs S1d: 0.74 ± 0.12; S3d: 0.60 ± 0.18 µg/L; P < 0.05) and IGF-1 (T1d: 168.94 ± 65.67; T3d: 201.56 ± 64.98 µg/L vs S1d: 116.72 ± 13.96; S3d: 107.50 ± 23.53 µg/L; P < 0.05) and expression of liver IGF-1 mRNA (T1d: 0.98 ± 0.20; T3d: 1.76 ± 0.17 vs S1d: 0.38 ± 0.09; S3d: 0.46 ± 0.10; P < 0.05). These findings indicate that treatment with rhGH had beneficial effects on the maintenance of the integrity of the intestinal mucosa barrier in septic rats.